2015
DOI: 10.3749/canmin.1400086
|View full text |Cite
|
Sign up to set email alerts
|

Mineral Ecology: Chance and Necessity in the Mineral Diversity of Terrestrial Planets

Abstract: Four factors contribute to the roles played by chance and necessity in determining mineral distribution and diversity at or near the surfaces of terrestrial planets: (1) crystal chemical characteristics; (2) mineral stability ranges; (3) the probability of occurrence for rare minerals; and (4) stellar and planetary stoichiometries in extrasolar systems.The most abundant elements generally have the largest numbers of mineral species, as modeled by relationships for Earth's upper continental crust (E) and the Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
65
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3
1

Relationship

3
4

Authors

Journals

citations
Cited by 81 publications
(70 citation statements)
references
References 145 publications
2
65
0
Order By: Relevance
“…By contrast, 22 % of mineral species have been found at only one locality and 12 % are found at only two localities, while more than half of all mineral species are found at five or fewer localities. Hazen et al (2015) proposed that the frequency distribution of mineral species with rare occurrence indicates that many more mineral species are yet to be discovered, have occurred in the past but are lacking on Earth today, or never formed owing to chance events.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…By contrast, 22 % of mineral species have been found at only one locality and 12 % are found at only two localities, while more than half of all mineral species are found at five or fewer localities. Hazen et al (2015) proposed that the frequency distribution of mineral species with rare occurrence indicates that many more mineral species are yet to be discovered, have occurred in the past but are lacking on Earth today, or never formed owing to chance events.…”
Section: Introductionmentioning
confidence: 98%
“…Mineral diversity is defined as the number of different mineral species, each of which has a unique combination of crystal structure and chemical composition as approved by the International Mineralogical Association (http://rruff.info/ima). Deterministic factors in mineral diversity are illustrated by the positive correlation between the abundances of crustal elements and the numbers of mineral species containing those elements (Hazen et al 2015). The most common and volumetrically significant minerals, which form from the most abundant crustal chemical elements (including oxygen, silicon, iron, magnesium, aluminum, and calcium), are known as the rock-forming minerals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous authors have identified a correlation between the crustal abundance of an element and the number of mineral species incorporating that element ( Fig. 1; Yaroshevsky and Bulakh 1994;Higgins and Smith 2010;Christy 2015;Hazen et al 2015).…”
Section: Introductionmentioning
confidence: 94%
“…Earth's mineralogical diversity and distribution arise from both deterministic processes and frozen accidents (Grew and Hazen 2014;Hazen et al 2015). For example, chance and necessity both play a role in the distribution of mineral species among the 72 essential mineral-forming chemical elements.…”
Section: Introductionmentioning
confidence: 99%